2005
DOI: 10.1017/s0952523805223027
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of plasma membrane Ca2+ ATPase isoforms in the neural retina of the postnatal rat

Abstract: Calcium ion~Ca 2ϩ ! signaling has been widely implicated in developmental events in the retina, but little is known about the specific mechanisms utilized by developing neurons to decrease intracellular Ca 2ϩ . Using immunocytochemistry, we determined the expression profiles of all known isoforms of a key Ca 2ϩ transporter, the plasma membrane Ca 2ϩ ATPase~PMCA!, in the rat retina. During the first postnatal week, the four PMCA isoforms were expressed in patterns that differed from their expression in the adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 70 publications
0
19
0
Order By: Relevance
“…To further characterize this homeostatic matrix, in the present work we investigated the expression pattern and the function of plasma membrane Ca 2+ ATPases in various gastric and colon cancer cell lines, and studied the effect of cell differentiation on their expression and activity. Implication of PMCAs in the differentiation of various tissue/cell types has already been published [27][28][29][30][31][32][33]. Our studies, focused on gastric/colon carcinomas, indicate that the major PMCA isoform expressed in these cancer cell lines is PMCA1b, whereas PMCA4b is expressed only at a reduced level.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…To further characterize this homeostatic matrix, in the present work we investigated the expression pattern and the function of plasma membrane Ca 2+ ATPases in various gastric and colon cancer cell lines, and studied the effect of cell differentiation on their expression and activity. Implication of PMCAs in the differentiation of various tissue/cell types has already been published [27][28][29][30][31][32][33]. Our studies, focused on gastric/colon carcinomas, indicate that the major PMCA isoform expressed in these cancer cell lines is PMCA1b, whereas PMCA4b is expressed only at a reduced level.…”
Section: Introductionmentioning
confidence: 69%
“…Modulations of PMCA expression have been observed during neuronal [27,28] and retinal [29] maturation, in myogenic [30], megakaryoblastoid [31], osteoblast-like [32] and trophoblast-like [33] differentiation models, as well as in cornea [84], in lactating mammary tissue [85] and oral and breast cancer [86,87]. In addition, marked induction of the expression of the SERCA3 endoplasmic reticulum Ca 2+ ATPases has been shown earlier during megakaryocytopoiesis [88], during cell differentiation in various leukemia [21,42] and gastric/ colon cancer cells ( [21,22,89].…”
Section: Discussionmentioning
confidence: 99%
“…To prevent overload and cell death, this calcium must be buffered and extruded. In the outer segment, calcium is extruded by a Na/Ca exchanger, whereas inner segment and synaptic terminal extrusion relies principally on PMCA [138,158,172,173]. PMCA are concentrated along the flanks of the terminal and appear to be absent from active zones of the ribbon synapse [135,174].…”
Section: Intracellular Calcium Handlingmentioning
confidence: 99%
“…Previous studies suggested that all four PMCA isoforms are expressed in the vertebrate retina (Križaj et al, 2002(Križaj et al, , 2004Rentería et al, 2005). Quantitative real-time RT-PCR was performed to assess the abundance of PMCA transcripts in the mouse retina.…”
Section: Pmca2 Is Abundant In the Retina But Is Not Required For Normmentioning
confidence: 99%
“…Given the prominent PMCA2 expression in retinal neurons (Križaj et al, 2002), its upregulation during retinal development (Rentería et al, 2005) and its key role in development and function of the cochlea and vestibular system (Street et al, 1998), which share a number of signaling elements with the retina (Zenisek et al, 2003;El-Amraoui and Petit, 2005), we hypothesized that PMCA2 modulates the establishment of retinal circuits in the developing retina as well as light responses at mature retinal synapses. To test this hypothesis, we analyzed retinal development and transmission of light-evoked signals in control and dfw 2J mice.…”
Section: Introductionmentioning
confidence: 99%